Urban infrastructure and economic development: Experimental evidence from street pavement - Marco Gonzalez-Navarro; Climent Quintana-Domeque (Institute for the Study of Labor (IZA), 2010)
We design an infrastructure experiment in Mexico to evaluate the impact of street pavement on housing values and household outcomes. We find that the provision of street pavement raises housing values by 16% and land values by 54%, according to professional appraisals. Using homeowner valuations, we estimate the impact of pavement on housing values to be 25%. At the household level, street paving increased the use of collateral-based credit and average loan size. Additionally, among households on paved streets vehicle ownership went up by 40%, while the number of durable goods augmented by 12% as a result of pavement. We provide compelling evidence that the mechanism explaining the durable goods increase is the credit channel: the raise in durable goods as well as in credit use was only present among households with access to financial services at baseline. This suggests that increments in the value of collateral are not sufficient to expand credit use in this context. Access to the financial sector is necessary for street pavement to be reflected in higher consumption of durable goods. Finally, we estimate the private gains to land plots on paved streets to be 109% of construction costs, which can have important implications for urban infrastructure financing.
Keywords: C92; C93; H41; O12; O15; 330; randomized controlled trial; street pavement; home values; durable goods; credit